Modern colposcopy : textbook & atlas - Mayeaux, E. J.; Cox, J. Thomas (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2012)
"The first two editions of this book were published by the American Society for Colposcopy and Cervical Pathology (ASCCP). This product is considered the standard of colposcopy and has the reputation of being the best selling educational teaching module_ for the physician, resident, or advanced practice clinician who wishes to bridge the gap between the obvious need for increased early detection of cervical, vaginal, and vulvar disease and the intensive education required for colposcopy.__The purpose of the society and the book is to provide education about the lower genital tract through the use of colposcopy. This includes the disciplines of pathology, cytology, cytogenetics, preventive medicine, basic research, gynecologic oncology, and endocrinology which are relevant to the understanding of the pathophysiology of the disease processes of the lower genital tract"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Colposcopy -- Atlases; Electronic books